Virus-like particle vaccines with epitopes from porcine epidemic virus and transmissible gastroenteritis virus incorporated into self-assembling ADDomer platform provide clinical immune responses in piglets - Du, Pengfei; Yan, Quanhui; Zhang, Xiao-Ai; Zeng, Weijun; Xie, Kaiyuan; Yuan, Zhongmao; Liu, Xiaodi; Liu, Xueyi; Zhang, Lihong; Wu, Keke; Li, Xiaowen; Fan, Shuangqi; et al. (Frontiers in Immunology, 2023)
Introduction Porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV) are major intestinal coronaviruses that cause vomiting, diarrhea, dehydration, and mortality in piglets. These viruses coexist and lead to significant economic losses in the swine industry. Virus-like particles (VLPs) have emerged as promising alternatives to conventional inactivated vaccines due to their exceptional safety, efficacy, and ability to provide multi-disease protection with a single dose. Methods Our study focused on specific antigenic epitopes from the PEDV S protein (SS2 and 2C10 regions) and the TGEV S protein (A and D sites) as target candidates. These epitopes were integrated into the ADDomer framework, and we successfully generated recombinant proteins AD, AD-P, AD-T, and AD-PT using the baculovirus expression vector system (BEVS). By meticulously optimizing conditions in High Five cells, we successfully expressed and purified the recombinant proteins. Subsequently, we developed the recombinant ADDomer-VLP vaccine and conducted a comprehensive evaluation of its efficacy in piglets. Results Following ultrafiltration concentration and sucrose gradient centrifugation purification, the recombinant proteins self-assembled into VLPs as observed by transmission electron microscopy (TEM). Administration of the vaccine did not result in any adverse reactions in the immunized piglets. Additionally, no significant instances of fever were detected in any of the experimental groups, and there were no notable changes in average daily weight gain compared to the control group that received PBS. The recombinant ADDomer-VLP vaccines demonstrated strong immunogenicity, effectively stimulating the production of neutralizing antibodies against both PEDV and TGEV. Moreover, the recombinant ADDomer-VLP vaccine induced elevated levels of IFN-γ, IL-2, and IL-4, and enhanced cytotoxic T lymphocyte (CTL) activity in the peripheral blood of piglets. Discussion These recombinant VLPs have demonstrated the ability to induce strong cellular and humoral immune responses in piglets, making them an incredibly promising platform for the rapid and simplified development of epitope vaccines.